Pituitary Transcriptome Analysis of Genes and Pathways Related to Traits at the First Egg in Kangle Yellow Chicken - Jinge MA; Lan LAN; Zige LIU; Jiguo XU (Guangdong nongye kexue)
【Objective】This study focus on Kangle yellow chickens, using transcriptome sequencing technology to deeply analyze the differences in pituitary transcriptome expression profiles of laying and pre-laying individuals at 154 days of age, aiming to screen the genes and signal pathways closely related to laying traits in the pituitary gland.【Method】Transcriptomic sequencing was performed on the pituitary tissues of 154-day-old Kangle yellow chickens using Illumian NovaSeq6000 sequencing platform. Functional annotation and protein network interaction analysis were performed on the selected differentially expressed genes, and RT-qPCR was used to validate gene expression levels.【Result】From 21 168 713 to 23 657 558 clean reads were obtained from both samples, and 23 447 genes were detected as expressed in pituitary tissue, including 222 marker genes classified as 8 large pituitary cell clusters. A total of 119 genes were obtained by screening and showed significant differential expression between laying and pre-laying Kangle yellow chickens, with 46 genes downregulated, and TRPC4 and TYRP1 were the genes with the highest upper and downregulation differences, respectively. GO functional enrichment analysis showed that the differentially expressed genes were mainly enriched in tube development, heart development, overall components of the membrane and nucleotide binding, etc. KEGG pathway enrichment analysis found that the differentially expressed genes were significantly enriched in signaling pathways including phagosomes, cellular senescence, cell adhesion molecules, endocytosis, and herpes simplex virus type 1 infection. Protein interaction analysis identified 14 of 119 differentially expressed genes with EPHA10, OVCH 1 and FGB as core proteins in the interaction network. By comprehensive analysis, 12 important candidate genes related to open birth traits were identified, namely POMC, CHGA, GRP, GH, CGA, PRL, CST3, CARTPT, TRPC4, PRKAA2, HTR1B and IGFBP5. RT-qPCR result showed that the expression trend of seven genes were consistent with transcriptome sequencing.【Conclusion】By analyzing the transcriptome sequencing results of the pituitary tissue of Kangle yellow Chicken, 12 candidate genes and 8 key gene pathways were screened, which provided solid data support for further exploring the molecular mechanism of regulating laying traits by the pituitary tissue genes in chicken.